Molecular Dynamics Simulations of Atomistic Detailed Hydration Structures of Poly(vinyl methyl ether) - Wu, Rongliang; Qiu, Xinlong; Zeng, Xiguo; Kong, Bin; Yang, Xiaozhen (My University, 2015)
Molecular dynamics simulations have been performed on the aqueous solutions of Poly(vinyl methyl ether) (PVME) at various concentrations. Both radial and spatial distribution functions are used to investigate the detailed hydration structures. The structures of water are found to get increasingly concentrated when polymers are introduced and the water motions are severely hindered by the polymer matrix. At low concentrations, larger populations of tt conformers in meso dyads than those at higher concentrations are found and this phenomenon is believed to be due to the increase of water molecule bonding to two ether oxygens in meso dyad. At higher concentrations the sizes and conformations of polymers are quite similar with those in bulk. A transition of hydrogen bond fractions between PVME and water at around the concentration of 0.3 is observed and this value coincides perfectly well with the results of conformational analysis and Raman spectra. Second neighbor hydrogen bond statistics showed that complicated hydrogen bond networks take the lead at low concentrations, but single hydrogen bonds as well as isolated clusters composed of 2-4 water molecules are found common around each polymer repeat unit.
Keywords: Molecular dynamics; PVME; Hydration structure; Solvation